Efeitos da estimulação elétrica na adaptação do músculo esquelético desnervado : implicações sobre a expressão gênica - Russo, Thiago Luiz de (2008)
Recovery denervated skeletal muscles is a challenge to rehabilitation. The degenerative changes on muscle tissue due to denervation cause muscle fiber atrophy and force generating incapacity impairing the individual daily life activities. Design strategies to treat denervated muscles are important to Physical Therapy. Electrical stimulation (ES) is a resource largely recommended to treat denervated muscles in humans, nevertheless, its effects and mechanisms on muscle adaptation are unclear. The aim of this thesis was to evaluate the effects of ES, applied as used in clinical-like situations, e.g., during single sessions, using surface electrodes and considering the changes in muscle excitability, on the denervated skeletal muscle adaptation in rat. The characterization of the muscle excitability pattern was used to choose the best electrical parameters. Histochemistry and immunohistochemistry tecnics were used to verify the morphology of denervated muscles submitted to ES. Furthermore, the real time polymerase chain reaction (PCR) analysis was used to evaluate the expression of important muscular genes, such as myoD, atrogin-1, metalloproteinase-2 and myostatin. ES was able to regulate many genes on rat denervated muscles; however ES neither avoid muscle fiber atrophy nor detain connective tissue proliferation in theses muscles. The results of this thesis have brought significative contributions to understand the mechanisms of ES, as recommended in rehabilitation, on denervated muscle.